3. OUTCOME OF UNILATERAL BIPORTAL ENDOSCOPIC DECOMPRESSION FOR DEGENERATIVE LUMBAR CANAL STENOSIS (Vietnam Journal of Community Medicine, 2024)
Background: Lumbar spinal stenosis is a common surgical indication among the elderly. The trend towards minimally invasive surgery is becoming more prominent, with unilateral biportal endoscopic (UBE) spinal surgery emerging as a promising technique. UBE decompression for lumbar spinal stenosis is an innovative method that offers numerous advantages.            Objectives: This study evaluates the clinical outcomes of patients with lumbar canal stenosis treated using the UBE decompression technique.            Methods: We conducted a case series study involving 30 patients with lumbar spinal stenosis who underwent UBE decompression at the University Medical Center, Ho Chi Minh City, between January 2019 and July 2022. We assessed preoperative and postoperative Visual Analog Scale (VAS) scores for back and leg pain, Oswestry Disability Index (ODI) scores, and Macnab criteria at the final follow-up.            Results: The mean postoperative follow-up duration was 17.3 ± 9.4 months (range: 6–41 months). The average operative time was 144.1 ± 57.3 minutes (range: 50–260 minutes), and the mean hospital stay was 3.97 ± 2.04 days (range: 1–11 days). The mean VAS score for leg pain decreased significantly from 6.63 ± 2.66 preoperatively to 0.79 ± 1.01 postoperatively, while the VAS score for back pain dropped from 7.00 ± 1.95 to 1.10 ± 1.11. The mean ODI score improved significantly from 62.55 ± 9.68% preoperatively to 22.31 ± 14.72% at 6 months post-surgery and 21.06 ± 15.67% at the final follow-up. According to the modified Macnab criteria, 46.6% of patients achieved excellent outcomes, 26.7% good, and 26.7% fair. Radiological assessments showed significant improvements in the anteroposterior diameter and cross-sectional area of the spinal canal, with the diameter increasing from 4.65 ± 1.21 mm to 8.93 ± 3.32 mm (p
Keywords: Unilateral biportal endoscopic spine surgery; lumbar canal stenosis; minimally invasive spine surgery